THE INCA ADMINISTRATIVE CENTER OF TAMBO VIEJO - Menzel, Dorothy (2012)
In this article we present the results of the archaeological studies carried out at the Inca administrative center of Tambo Viejo, the only facility of its character built by the Inca in the Acari Valley of the Peruvian south coast region. This study reveals, among others, the architectural complexity of the site and its enormous size. Likewise, this study demonstrates that Tambo Viejo has a long sequence of human occupation that began early in the Early Intermediate period and continued to colonial times. In this paper we evaluate the Inca ocupation of the site, taking into consideration the architecture. This analysis demonstrates that Tambo Viejo was established following an Inca plan; however, the architecture is local, suggesting that the builders of the site were from Acari. This observation allows us to argue that the Inca administration adapted to local construction patterns.